THU0017 Chloroquine resistance in human cem (t) cells is mediated by multidrug resistance protein 1. (1st June 2001) - Jansen, G; Scheper, RJ; Dijkmans, B
Abstract : Background: Drug resistance may play a role in the lack of efficacy of Disease Modifying Anti Rheumatic Drugs (DMARDs). Objectives: (1) Delineate mechanism of drug resistance to chloroquine (CHQ) and (2) does CHQ resistance confer resistance to other DMARDs. Methods: Human CEM (T) cells were made resistant to CHQ following a 4 months in vitro exposure to stepwise increasing extracellular CHQ concentrations. Results: CHQ resistant CEM cells (CEM/CHQ) displayed 3.3-fold resistance to CHQ compared to CEM cells (IC50 : 129 μM vs 39 μM, respectively, following 72 h drug exposure). The resistant phenotype was stable for at least one month when CEM/CHQ cells were grown in the absence of CHQ. CEM/CHQ cells exhibited full sensitivity to methotrexate (MTX) and were even collaterally sensitive (1.7-fold) to sulfasalazine. Interestingly, CEM/CHQ cells displayed cross-resistance to doxorubicin and daunorubicin, suggesting that multidrug resistance proteins play a role in the resistant phenotype. In fact, immunological detection (Western blots) revealed a markedly increased expression of multidrug resistance protein 1 (MRP1) in CEM/CHQ cells compared to CEM cells. Involvement of MRP1 in CHQ resistance was further illustrated by observations that inhibitors of MRP1, probenecid and MK571, were able to reverse CHQ resistance in CEM/CHQ cells. Beyond MRP1, we noted that also cells transfected with MRP2 and MRP3 displayed resistance to CHQ (2.1- and 1.8-fold, respectively). Conclusion: Overexpression of multidrug resistance proteins (MRP1, MRP2 and MRP3) can confer in vitro resistance to CHQ and should be considered as a mechanism of lack of drug efficacy in a clinical setting.